The Company Value Considered from Economic Value Added (EVA), Market Value Added (MVA) and Company Size: Study on the Food and Beverage Sub-Sector Manufacturing Companies - Purnama Agustina, Intan Purnama Agustina; Widiastuti, Anna (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2024)
This study aims to examine the effects of Economic Value Added (EVA), Market Value Added (MVA), and company size towards the company value on the food and beverage sub-sector manufacturing companies, listed on the Indonesia Stock Exchange for the 2018-2021 period. It is the descriptive research using the quantitative approach. The research population involved the food and beverage sub- sector manufacturing companies, listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. Then, the sampling technique used purposive sampling, and the number of research samples was 44 companies. The used data were the secondary data which were obtained from the Indonesia Stock Exchange (IDX), and the data analysis was multiple linear regression analysis by using Eviews 10. The research results showed that (1) Economic Value Added had no significant effect on the company Value. (2) Market Value Added had a significant positive effect on the company Value. (3) Company Size had a significant negative effect on the company Value.